Noninvasive Differential Diagnosis of Pulmonary Nodules Using the Standardized Uptake Value Index - Shiono, Satoshi (Ann Thorac Cardiovasc Surg, 2015)
Objectives: We previously showed that the standardized uptake value (SUV) index, which was defined as the ratio of the maximum SUV of the tumor to mean SUV of the liver, was a surrogate marker of lung cancer aggressiveness. In this study of patients with pulmonary nodules (PNs), we explored whether the SUV index could be used to differentiate small malignant from small benign PNs Methods: A total of 284 patients with solitary PNs ≤2 cm in size underwent positron emission tomography/computed tomography and surgery. The associations between pathological findings and clinical factors were evaluated. Results: The median SUV indices of lung cancer, metastatic PNs and benign nodules were 1.2, 1.5, and 0.6, respectively (P <0.01). A SUV index cut-off value of 1.2 was used to differentiate benign from malignant nodules. When patients were grouped according to SUV index cut-off values of <1.2 or ≥1.2, the following cases were false-negative: lung adenocarcinoma (P <0.01), kidney as primary site (P <0.01), and metastatic PNs with long disease-free survival (P = 0.02). Conclusions: As a noninvasive diagnostic marker, the SUV index was found to be useful for differentiating benign from malignant small PNs.